1996
DOI: 10.1097/00005373-199605000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Trauma and Injury Severity Score in Blunt Trauma Patients by Using a Canadian Trauma Registry

Abstract: TRISS demonstrated satisfactory performance in a Canadian blunt trauma population. Although revision of coefficients led to a better fit on the Hosmer-Lemeshow statistic, ROC curves demonstrated virtually identical performance of the MTOS and Ontario-based TRISS models. The poor performance of the Revised Trauma Score and the observation that its use led to the exclusion of 40% of cases with a higher mortality raises concerns regarding its use in the TRISS model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
10

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 12 publications
2
23
0
10
Order By: Relevance
“…Most studies found that TRISS discriminates well between survivors and nonsurvivors but lacks predictive reliability. 8,[28][29][30] The question has been raised about whether it is more relevant and accurate to generate TRISS equation coefficients that are unique to particular trauma data sources, rather than relying on the originally published MTOS coefficients. The development of new TRISS coefficients for analysis of the outcomes of individual trauma data sets would seem logical because different regions, trauma centers, etc., are likely to differ in the casemix of patients seen, injury types, patient types, and severity of injuries seen.…”
Section: Practical Applications Of Trissmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies found that TRISS discriminates well between survivors and nonsurvivors but lacks predictive reliability. 8,[28][29][30] The question has been raised about whether it is more relevant and accurate to generate TRISS equation coefficients that are unique to particular trauma data sources, rather than relying on the originally published MTOS coefficients. The development of new TRISS coefficients for analysis of the outcomes of individual trauma data sets would seem logical because different regions, trauma centers, etc., are likely to differ in the casemix of patients seen, injury types, patient types, and severity of injuries seen.…”
Section: Practical Applications Of Trissmentioning
confidence: 99%
“…[28][29][30] Although the coefficients developed by individual studies were quite different from the MTOS coefficients, the pattern of findings remains the same with marginally improved discrimination but generally poor predictive reliability.…”
Section: Practical Applications Of Trissmentioning
confidence: 99%
“…Table 1 shows predominance of retrospective (87.5%) (14)(15)(16)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) national multi-center studies (62,5%) (18)(19)(20)(22)(23)(25)(26)(27)(28)(29)(30)(31)(32)(33)35,38,(41)(42)(44)(45) , using databases as sources (81.3%) (19)(20)(21)…”
Section: Resultsmentioning
confidence: 99%
“…(24,(68)(69)(70)(71)(72) . A maioria desses estudos foi desenvolvida e publicada nos EUA (11,37,39,41,43,(57)(58)(60)(61)(63)(64)(65)(66)(67)(68)(71)(72)(73)(74) , sendo, dessa forma, o inglês o idioma mais frequente de publicação (11,19,24,33,(35)(36)(37)(38)(39)(40)(41)(42)(43)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)…”
Section: Lista De Ilustraçõesunclassified
“…Houve predomínio de estudos que trabalharam com apenas uma equação modificada (43,8%) (11,24,(33)(34)38,(41)(42)58,60,(63)(64)(66)(67)72) , seguidos por 2 equações (18,8%) (37,61,62,71,73,74) . …”
Section: Lista De Ilustraçõesunclassified